Efficacy and Tolerance of Sirolimus (Rapamycin) for Extracranial Arteriovenous Malformations in Children and Adults - Romain Gabeff; Olivia Boccara; Véronique Soupre; Gérard Lorette; Christine Bodemer; Denis Herbreteau; Elsa Tavernier; Annabel Maruani (Medical Journals Sweden, 2019)
Managing extracranial arteriovenous malformations is challenging. Sirolimus (rapamycin) is increasingly being used when surgery and embolization are not advised. Because of its anti-angiogenic properties here we report all extracranial arteriovenous malformation cases treated with sirolimus in 2 French tertiary centers for vascular anomalies. The outcomes were efficacy (complete, partial, no response) based on arteriovenous malformation volume and necrosis/hemorrhage and side effects. We retrospectively included 10 patients (7 children). The sirolimus dose ranged from 0.6 to 3.5 mg/m2. Median (interquartile range [IQR]) treatment time was 24.5 (4.5; 35) months. Five patients showed no response and 5 showed partial response at a median (IQR) of 3 (1; 5) months followed in 2 cases by therapeutic resistance (i.e., progressive disease after 9 and 24 months of treatment). The most frequent side effect was mouth ulcers. This study shows poor efficacy of sirolimus for treating extracranial arteriovenous malformations.